Pemanfaatan Data Analytics dalam Pengambilan Keputusan Bisnis: Sebuah Kajian Literatur - Fadil Azury Farega Rambe; Nastiar Saputra Rangkuti; Raihan Ananda Azma; Muhammad Rizal (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2026)
The digital transformation in the era of Industry 4.0 has positioned data as a strategic resource that plays a pivotal role in supporting business decision-making. This study aims to explore the contributions, benefits, and challenges of implementing big data analytics in the contexts of fraud detection, audit quality enhancement, and business strategy optimization. Employing a descriptive qualitative approach through a systematic literature review of various empirical and conceptual studies, the findings reveal that big data analytics significantly improves audit effectiveness, accelerates data analysis, and strengthens oversight functions through the integration ofmachine learning and deep learning technologies. Furthermore, data analytics functions as a strategic instrument for risk management, financial forecasting, and enhancing organizational competitiveness. However, its implementation in Indonesia still encounters challenges such as limited digital infrastructure, low data literacy, and insufficient data-driven organizational culture. The findings underscore that the success of big data analytics adoption relies on the synergy between technology, human resources, and organizational strategies, aligned with the Technology-Organization-Environment (TOE) framework. Practically, this study recommends investment in digital infrastructure, continuous capacity building for human resources, and fostering a data-driven culture as fundamental steps to strengthen governance quality, audit effectiveness, and business decision-making in the digital era..